The effect of proportion of soy milk with sweet corn milk on physicochemical and organoleptic properties of vegetable ice cream - Andini, Lale Mustika; Alamsyah, Ahmad; Handito, Dody (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2024)
The purpose of this study was to determine the effect of proportion of soy milk with sweet corn milk on physicochemical and organoleptic properties of vegetable ice cream. The design used a completely randomized block design with 5 treatments and 4 replications. Treatment were proportion of soy milk with sweet corn milk i.e. P1 (100%: 0%), P2 (75%: 25%), P3 (50%: 50%), P4 (25%: 75%) and P5 (0%: 100%). Parameters observed included protein content, total dissolved solids, overrun, resistance, color and organoleptic (color, taste, odor and mouthfeel). Data were analyzed using analysis ofvariance and if significantly differentthen tested by orthogonal polynomial method (MOP) for all parameters and Honestly Significance Differences (HSD) for organoleptic test. The results showed that various treatments had significant effect on protein content, overrun, color (°Huevalue), color (hedonic) and gave no significant effect on total soluble solids, resistance, color (L value), taste, mouthfeel and smell (hedonic). Each treatment did not meet the SNI quality standard of ice cream but resistance test gave result which fulfill SNI quality standard of ice cream. Keywords :Ice cream, soy milk, sweet corn milk